Organizational study on voice over internet protocol (voip) in Universiti Teknologi Mara (UiTM) Shah Alam - Md Raus, Mohd Ikhsan; Abd Aziz, Muhd Eizan Shafiq (University Teknology MARA Pahang, 2011)
Voice over Internet Protocol (VoIP) becomes popular communication solution. A great evolution on Internet technology has brought up this technology to emerge and expand since it uses data network to transmit voice from sender to receiver which means voice and data travel using a single medium. By upgrading existing PBX to IP PBX, it makes VoIP to easily blend into existing communication technology. VoIP services widely used in United States, European and Asian countries. Informal observation and interviews discovered several organizations in Malaysia have already used VoIP. Therefore, it is a matter of time to UiTM to use this technology as a major communication medium. With almost 27 campuses nationwide, communicate through PSTN, at the same time subscribing such a huge amount of Internet bandwidth, there are opportunities for UiTM to replace PSTN as its major communication medium or at least allowing these two technologies to work together. The reason VoIP can be a great option is because it promotes cost effective in communication especially organization such as UiTM that have many branches.